Immune-related adverse events correlate with clinical outcomes in NSCLC patients treated with nivolumab: The Italian NSCLC expanded access program. (February 2020) - Baldini, Editta; Lunghi, Alice; Cortesi, Enrico; Turci, Daniele; Signorelli, Diego; Stati, Valeria; Melotti, Barbara; Ricciuti, Biagio; Frassoldati, Antonio; Romano, Giampiero; Ceresoli, Giovanni Luca; Illiano, Alfonso; et al.
Highlights: Immunotherapy significantly improved the outcome of advanced NSCLC. 1959 advanced NSCLC patients received Nivolumab in the Italian expanded access program. Activation of the immune system through the appearance of irAEs correlated with outcome. Abstract: Objectives: The incidence of any and of severe-grade immune-related adverse events (irAEs) with second-line nivolumab monotherapy is 31–65 % and 2–5 % respectively. While potentially serious and even fatal, in the absence of an appropriate therapy, such events might be indicators of the activation of the immune system and, potentially, of efficacy. Materials and Methods: We collected the records of 1959 non-small-cell lung cancer (NSCLC) patients treated with nivolumab in the Italian expanded access program, and we registered the appearance of any and of severe grade irAEs. We retrospectively searched for correlations between toxicity and efficacy parameters by using Cox's regression analysis. Results: Overall, 342 (17.8%) patients developed an irAE of any grade. We observed that patients developing irAE of any grade achieved a significantly higher response rate (RR 27.2% vs 15.2%; p < 0.0001), disease control rate (DCR 60.5% vs 40.2%; p < 0.0001), median progression-free survival (mPFS 6.0 months [95% CI 4.9–7.1] vs 3.0 [95% CI: 2.8–3.2], p < 0.0001) and median overall survival (mOS 16.7 months [95% CI: 13.5–19.9] vs 9.4 [95% CI: 8.4–10.4], p < 0.00001) compared to patients who did not. At multivariate analysis the development of an irAE remained an independent indicator of nivolumab efficacy (HR 1.44 [95% CI: 1.22–1.71] p < 0.0001). Conclusions: This report, performed in Caucasian NSCLC patients, showed that the appearance of irAEs correlated with outcome.